2023
DOI: 10.1007/s00705-023-05709-6
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant fiber-1 protein of fowl adenovirus serotype 4 induces high levels of neutralizing antibodies in immunized chickens

Abstract: Virulent fowl adenovirus serotype 4 (FAdV-4) causes hydropericardium syndrome (HPS) with high mortality in chickens, leading to significant economic losses to the poultry industry. The development of an effective vaccine is essential for successful disease control. Here, we produced recombinant fiber-1 protein of FAdV-4, isolated from a Japanese HPS outbreak strain, JP/LVP-1/96, using a baculovirus expression system and evaluated its immunogenicity and protective efficacy. Recombinant fiber-1 protein induced h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…All of these revealed that Fiber2 subunit vaccine could induce the cellular immune responses and humoral immune response ( Yin et al, 2021 ). However, Fiber1 is also immunogenic and has a protective effect against FAdV-4, it can induce high level of neutralizing antibodies in immunized chickens ( Wang et al, 2018 ; Watanabe et al, 2023 ). Both Fiber2 and Fiber1 knob domains are their main functional areas and are key domains for their immune effects ( Song et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…All of these revealed that Fiber2 subunit vaccine could induce the cellular immune responses and humoral immune response ( Yin et al, 2021 ). However, Fiber1 is also immunogenic and has a protective effect against FAdV-4, it can induce high level of neutralizing antibodies in immunized chickens ( Wang et al, 2018 ; Watanabe et al, 2023 ). Both Fiber2 and Fiber1 knob domains are their main functional areas and are key domains for their immune effects ( Song et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%